dict1={'a':1,'b':2,'c':3}dict2={'b':2,'a':1,'c':3}dict1 is dict2的结果
A: True
B: False
A: True
B: False
举一反三
- dict1={'a':1,'b':2,'c':3}dict2={'b':2,'a':1,'c':3}dict1 is dict2的结果 A: True B: False
- 字典中添加元素( )。 A: DICT[3]=(1,2,3) B: DICT['4]=6:3 C: DICT[2]=2 D: DICT['1']=1
- dict={'1':1,'2':2} theCopy=dict dict['1']=5 sum=dict['1']+theCopy['1'] print(sum)
- dict = {'a': 1, 'b': 2, 'c': '3'}dict['d']=4print(dict)上述程序运行后的结果是: A: {'d': '4'} B: dict = {'a': 1, 'b': 2, 'c': '3', 'd': 4} C: dict = {'a': 1, 'b': 2, 'c': '3'} D: 报错
- 以下能正确的创建字典的是() A: dict={}.fromkeys((1,2)) B: dict={a:1,b:2,c:3} C: dict={{1,2}:1} D: dict=dict([1,2],[3,4])